Considerations and demands in the voice care of contemporary commercial singers in occupational health and safety aspects - Joanna Morawska; Ewa Niebudek-Bogusz; Wioletta Pietruszewska (Nofer Institute of Occupational Medicine, 2022)
Singers, classified as "vocal performers" are at an increased risk of developing voice disorders. The area of contemporary commercial singing has not been studied as extensively as classical singing. Non-classical singing is generally considered detrimental to vocal health and thus the information on challenges contemporary commercial singers (CCS) pose to otolaryngologists and other healthcare professionals is scarce. The authors present an overview of contemporary commercial singing styles in comparison to classical singing, discuss the notion of non-classical style being harmful to vocal health, present major risk factors associated with developing voice disorders in contemporary commercial singers, and outline the diagnostic process of vocal health assessment in this group of occupational voice users. Given that contemporary commercial singers constitute a unique and vast group of elite vocal performers, the authors stress the importance of raising awareness among healthcare professionals of the fact that these patients require special considerations for voice evaluation and treatment in the occupational health and safety framework. Med Pr. 2022;73(1):33-41